Intracranial Textiloma: Imaging Features and Literature Review - Agarwal, Vivek; Vyas, Sameer; Ahuja, Chirag Kamal; Bhatia, Vikas; Tripathi, Manjul; Salunke, Pravin; Tewari, Manoj Kumar (Indian Journal of Radiology and Imaging, 2021)
Background and Importance Intracranial textilomas are retained surgical sponges presenting as pseudomass lesions in postoperative patients usually with surrounding inflammatory reaction. Though rare, these are commonly misdiagnosed as postoperative hemorrhagic collections, abscesses, radionecrosis, or residual/recurrent mass lesions. We describe the imaging findings of intracranial textilomas diagnosed in four patients on follow-up postoperative imaging along with their characteristic imaging findings to help radiologists/neurosurgeons make accurate diagnosis.Clinical Presentation One patient had chronic headache without any focal neurological deficits. Rest of the patients were asymptomatic at the time of presentationConclusion In postoperative scans, possibility of textilomas should be considered apart from residual/recurrent lesions, postoperative abscesses, or radionecrosis. Correct and timely diagnosis is important for further treatment planning and patient care.
Keywords: textiloma; surgical sponges; pseudomass; postoperative